2014
DOI: 10.1002/pro.2471
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding study of a trimeric membrane protein AcrB

Abstract: The folding of a multi-domain trimeric a-helical membrane protein, Escherichia coli inner membrane protein AcrB, was investigated. AcrB contains both a transmembrane domain and a large periplasmic domain. Protein unfolding in sodium dodecyl sulfate (SDS) and urea was monitored using the intrinsic fluorescence and circular dichroism spectroscopy. The SDS denaturation curve displayed a sigmoidal profile, which could be fitted with a two-state unfolding model. To investigate the unfolding of separate domains, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…However, we have previously found that the presence of intersubunit disulfide bonds, which strengthen AcrB trimer stability by covalently linking the three subunits, has little effect on the transition point of AcrB unfolding monitored using fluorescence intensity. 25 The fluorescence intensity change indicates the exposure of previously hidden aromatic residues, which results from the disruption of the hydrophobic core or dissociation of subunits. There are two potential reasons that may lead to this observation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have previously found that the presence of intersubunit disulfide bonds, which strengthen AcrB trimer stability by covalently linking the three subunits, has little effect on the transition point of AcrB unfolding monitored using fluorescence intensity. 25 The fluorescence intensity change indicates the exposure of previously hidden aromatic residues, which results from the disruption of the hydrophobic core or dissociation of subunits. There are two potential reasons that may lead to this observation.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that the change of the fluorescence signal is largely contributed by aromatic residues in the soluble domain. 25 The unfolding of the transmembrane domain may not generate a detectable fluorescence signal change, as the change of microenvironment for Trp residues in the transmembrane domain upon unfolding is not likely to be as dramatic as for Trp residues in the soluble domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many membrane proteins have been successfully refolded after incubation in mild denaturants such as SDS (41), it is less common for a-helical membrane proteins to be successfully refolded to an active state after substantial unfolding (42). In some cases, native-like secondary structure can be restored, although reassociation of different subunits seems to be a limiting factor, as observed with the multidrug transporter, AcrB (43). Both HiGlpG and PsAarA exist as dimers in DDM (44); indeed, we observe a dimeric state for both HiGlpG and PsAarA upon refolding.…”
Section: Tertiary Structure and Activity Upon Refoldingmentioning
confidence: 99%
“…Interestingly, almost all suggest that oligomerization is a cooperative rather than sequential process. In unfolding and refolding studies of the tetrameric KscA using triflouroethanol (Valiyaveetil et al , 2002; Barrera et al , 2008) and of the trimeric AcrB using SDS and urea (Ye et al , 2014a), no intermediates were observed. Unfolding and refolding studies of AcrB and the ABC transporter BtuCD even suggested that oligomerization might be coupled with folding.…”
Section: Introductionmentioning
confidence: 99%